Potential geographical distribution of Cordyceps cicadae and its two hosts in China under climate change - Chen, Junyi; He, Donglan (Frontiers in Microbiology, 2025)
IntroductionThe fungus Cordyceps cicadae is both edible and medicinal.MethodsTo acquire a thorough comprehension of its distribution in China, two host insects, Macrosemia pieli and Platypleura kaempferi, were selected as biological factors potentially associated with its distribution, the ENMTools program was utilized to ascertain the principal environmental factors affecting the distribution of potentially suitable habitats. The possible geographic distributions in the present as well as in the 2030s, 2050s, and 2070s were then predicted using the optimized MaxEnt model.ResultsThe primary environmental variables were soil pH, mean diurnal range, annual precipitation, precipitation seasonality, annual mean temperature and precipitation of the driest month. C. cicadae thrived on steep slopes. and some of which also significantly affect the distribution of its two hosts. Most of the suitable habitats of C. cicadae and M. pieli were currently found in the subtropical monsoon zone. The SSP126, SSP370, and SSP585 scenarios were associated with positive, stable, and unfavorable impacts on the extent of suitable habitats for C. cicadae, respectively, and the suitability of P. kaempferi decreased under three different conditions. The expansion of the C. cicadae was observed in provinces bordering the middle and lower reaches of the Yellow River, as well as in Zhanjiang, Guangdong Province, and northern Yunnan Province. Conversely, its habitat contraction was mainly found in western Guangdong, southern Guangxi, northern Hainan, southwestern Yunnan, and areas bordering eastern Sichuan. The shared contraction regions with its two hosts were primarily located in western Guangdong, southern Guangxi, and southern Sichuan. Moreover, the future centroids were found at higher elevations than the present ones in the provinces of Jiangxi and Hunan.DiscussionIn light of climate change, this research held significance for the conservation and sustainable utilization of C. cicadae.